Perawatan Bangunan Fasilitas Umum di Desa Bencoy Kecamatan Cireunghas Kab. Sukabumi - Mulki Pangestu; M.Raiga Agusti Rustandi; Lisna; Moch Ichwan Setia (Universitas Nusa Putra & Persatuan Insinyur Indonesia, 2023)
Public facilities building is one of the buildings intended for the public, the public facilities are provided by the government for the common interest in daily activities. Therefore, the facilities must have comfort when used by all groups, In Indonesia, the maintenance of public facilities is not comprehensive enough so that there are some public facilities that are not well maintained. In my opinion, maintenance of these public facilities is important because it involves comfort when used by the community. Therefore we carry out maintenance on public facility buildings in Bencoy Village, Cireunghas District, Sukabumi Regency in order to create comfort for users of public facilities later. From the public facility building, we carried out renovations for approximately five days by compiling the interior and exterior design of the public facility building, then dismantling and repairing it according to the design, then adjusting the interior first, then adjusting the exterior and finally painting the interior and exterior of the building. further clean and clean the building of public facilities so that the realization of comfort for users of the building.